Analysis of Base Shear and Story Drift in the Low-Rise RC Structure - Bong, Phil Benson; Bali, Ika (President University, 2024)
Earthquakes frequently occur in Indonesia because it is an earthquake-prone area. Due to lateral load from an earthquake can cause a weakly constructed building to collapse. Designers often only consider tall buildings in designing earthquake-resistant building structures but ignore earthquake-resistant designing for low-rise buildings. This study focuses on the analysis of earthquake resistant structures with a case study of low-rise buildings in the form of a 3-story reinforced concrete (RC) building in the South Jakarta area. The objective of the study is to analyze the base shear and story drift of the structure due to lateral or earthquake loads. The structure is a reinforced concrete with the concrete compressive strength of = 30 MPa and longitudinal reinforcement of = 420 MPa and stirrups of = 280 MPa. This study uses equivalent static analysis manually and using ETABS 20.1.0 application. The results showed that three story buildings analyzed using equivalent static analysis method and using ETABS 20.1.0 application had almost the same results on horizontal forces with manual result of 1680.97 kN and ETABS of 1648.46 kN. The elastic story deflection and inelastic story drift in this study are still within safe limits because it is below the drift limit.